Factors Influencing the Choice between DOACs and LMWHs: A Survey of German Physicians on the Treatment of Cancer-Associated Venous Thromboembolism - Matzdorff, Axel; Langer, Florian (Hämostaseologie, 2020)
Recently direct-acting oral anticoagulants (DOACs) have become a new therapeutic option besides parenteral anticoagulants to treat cancer-associated venous thromboembolism (VTE). With this survey we wanted to identify factors influencing the choice between low-molecular-weight heparin and DOACs among physicians treating cancer patients. A questionnaire was presented at several medical educational activities on cancer care and VTE management between August 2018 and January 2019. One hundred fifteen physicians returned their surveys. The two most compelling arguments pro DOAC were when the patient had no chemotherapy and when he expressed unwillingness to apply injections. The two most important arguments against DOACs were if the patient had problems with taking oral medications or when he had a history of severe bleeding. This survey shows that future studies need to consider many more factors, particularly patient preferences and physician concerns on bleeding risk, to improve their applicability in daily practice.
Keywords: cancer-associated venous thromboembolism; direct oral anticoagulants; low-molecular-weight heparin